Leaf anatomy and histochemistry of Lippia citriodora (Verbenaceae) - Argyropoulou, C.; Akoumianaki-Ioannidou, A.; Christodoulakis, N.S.; Fasseas, C. (Australian Journal of Botany, 2010)
Lippia citriodora H.B.K. is an aromatic plant indigenous to South America. It is cultivated and commercialised as an ornamental for its lemon-like scent emitted from its leaves and flowers. The present morphoanatomical and histochemical study revealed that leaves of L. citriodora possess one type of setae (non-glandular) and at least five types of glandular trichomes, with the latter differing anatomically and in the composition of their secondary metabolites. Scanning electron microscopy revealed that the same types of trichomes exist also on the calyces. Histochemical tests indicate that the glandular trichomes contain a combination of terpenoids, flavonoids, carbohydrates, phenolics and alkaloids. However, within the vacuoles of the mesophyll cells, terpenoids, phenolics, flavonoids and tannins are stored. The presence of lamellar cytoplasmic inclusions in the mesophyll cells, possibly precursors of tannins stored in the vacuoles, is reported for the first time. © 2010 CSIRO.
Keywords: Aloysia triphylla; anatomy; Citrus limon; Cytoplasm; dicotyledon; indigenous population; Lippia; ornamental species; phytochemistry; scanning electron microscopy; secondary metabolite; Verbenaceae